Studying the Performance and Kinetic Values for Pollutant Removal Using Lab Scale Plant - Thapa, Bijay; Khatiwada, Nawa Raj; Malla, Rabin; Ghimire, Anish; Adhikari, Bikash (Kathmandu University Journal of Science, Engineering and Technology, 2020)
The present study aimed at determining performance and pollutant removal kinetics in the treatment of wastewater using a laboratory-scale continuous flow stirred tank reactor (CFSTR) based on activated sludge process (ASP). The waste activated sludge from the Guheshwori Wastewater Treatment Plant (WWTP) is used as a start-up seed sludge. The CFSTR is operated at varying solid retention time (SRT) of 1, 2, 3, 5, 7.5 and 10 days using synthetic wastewater prepared daily as an influent. Chemical Oxygen Demand (COD) and Total Kjeldahl Nitrogen (TKN) of the influent, effluent and Mixed Liquor Volatile Suspended Solids (MLVSS) of aeration tank are analyzed at various SRT to determine the respective kinetic coefficients. The COD and TKN removal increased with increasing SRT. The kinetic coefficients; maximum substrate utilization rate (k), the half velocity constant (Ks), cell yield coefficient (Y ) and decay coefficient (kd) have been found to be 1.61 g COD/g VSS · day, 87.22 mg/L, 0.50 g Volatile Suspended Solid (VSS)/g COD and 0.07 day-1 respectively for synthetic wastewater. Similarly, k, Ks, Y and kd for the treatment of wastewater from Guheswori WWTP have been observed to be 1.86 g COD/g VSS.day, 107.77 mg/L, 0.32 g VSS/g COD and 0.04 day-1.